Factor Price Frontiers with International Fragmentation of Multistage Production - Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2003)
I develop a generalized factor price frontier which incorporates endogenous adjustment of international fragmentation in multistage production, allowing for a continuum of stages. This allows us to address fragmentation, not only as an exogenous event, but also as an integral part of endogenous adjustment to a variety of changes not directly related to fragmentation. A two-dimensional general equilibrium analysis explores how the margin of fragmentation, as well as factor prices, respond to a change in the final output price, and to an improvement in the technology of fragmentation. A key distinction arises between the average and marginal labour intensity, respectively, of domestic production in the multistage industry. The paper identifies conditions under which outsourcing to a low-wage country is a friend or an enemy to domestic labour, as well as conditions under which the Jonesian magnification e.ects underlying the Stolper-Samuelson theorem are reinforced, or mitigated, by endogenous changes in the margin of fragmentation. Protection may result in a broader or a narrower range of stages produced domestically.
Keywords: D33; F11; F15; F23; 330; Globalisierung; Outsourcing; Faktorpreisausgleich; Welt